The Role of Transformational Leadership, Organizational Identification, Employee Voice, Psychological Capital, and Innovation Climate in Shaping Innovative Work Behavior in Public Sector Employees - Muhammad Suryanto; Riani Rachmawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In the face of rapid global changes and increasing social complexity, public sector organizations are required to continuously innovate to enhance service quality. This study aims to explore the influence of transformational leadership on innovative work behavior in the public sector, considering the mediating roles of organizational identification, employee voice, and psychological capital, as well as the moderating role of innovation climate. Data were collected through an online questionnaire completed by 319 civil servants at the Secretariat General of a ministry responsible for managing state finances. Following data screening and cleansing, 313 valid responses were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the SmartPLS 4.0 application. The results indicate that transformational leadership does not have a significant direct effect on innovative work behavior. However, a significant positive influence is observed through the mediation of employee voice and psychological capital. Furthermore, the influence of transformational leadership on innovative work behavior becomes stronger when employees work in a high innovation climate. This study provides theoretical and empirical insights into human resource management, particularly in understanding the determinants of innovative work behavior to support the development of innovative and high-quality public services.